The relationship between performance and flow state in tennis competition - Koehn, S.; Morris, T. (The Journal of Sports Medicine and Physical Fitness, 2012)
AIM: The study aimed to examine 1) the validity of the nine-factor flow model in tennis competition; 2) differences in flow state between athletes who won or lost their competition match; 3) the link between flow and subjective performance; and 4) flow dimensions as predictors of performance outcome METHODS: The sample consisted of 188 junior tennis players (115 male, 73 female) between 12 and 18 years of age. Participants` performance was recorded during junior ranking-list tournaments. Following the completion of a tennis competition match, participants completed the Flow State Scale-2 and a subjective performance outcome measure. RESULTS: Acceptable flow model fit indices of CFI, TLI, SRMR, and RMSEA were only found for winning athletes. The group of winning athletes scored significantly higher on all nine flow dimensions, except time transformation, than losing athletes, showing statistically significant differences for challenge-skills balance, clear goals, sense of control, and autotelic experience. Significant correlation coefficients were found between flow state and subjective performance assessments. The binary logistic regression revealed concentration on the task and sense of control to be significant predictors of performance outcome. The predictor variables explained 13% of the variance in games won. CONCLUSION: The study showed that athletes who win or lose perceived flow state differently. Studies using retrospective assessments need to be aware that subjective experience could be biased by performance outcomes. Pinpointing psychological variables and their impact on ecologically valid measures, such as performance results, would support the development of effective intervention studies to increase performance in sport competition.